The Faculty Role in Campus Unrest - Boruch, Robert F.; American Council on Education, Washington, DC. Office of Research (Washington, D.C. : Distributed by ERIC Clearinghouse, 1969)
Anecdotal evidence suggests that college faculty members are highly involved in student protests but there is little systematic data available to support or refute this contention. The current study was undertaken to document and assess the participation of faculty in student unrest phenomena. This report contains a summary of administrators' perceptions of the topic. Information was derived from responses to mailed questionnaires sent during 1968 to academic deans at 281 colleges and universities. The institutional sample was diverse; percentages were weighted in order to obtain population estimates. It was found that student protests occurred at slightly more than half the sampled institutions. Faculty representatives had a major role in administrative planning to deal with protests at about 25%, and provided information about the protest to the administration prior to the event in an equal number of cases. Faculty involvement with planning a protest was associated with occurrence of more peaceful types of demonstrations; correlations of faculty (or teaching assistant) planning and participation were smallest with physically violent and physical obstructionist protests. Faculty members were perceived as sympathetic supporters of protesters at about half the institutions and took leadership roles at 11%. Few deans felt that relations between faculty and administration had deteriorated as a result of the protest. The data indicate that some restructuring of faculty-administrative relations is warranted or desirable. (JS)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Activism; Administrative Policy; Demonstrations (Civil); Faculty; Higher Education